1989
DOI: 10.1161/01.str.20.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis detection in cerebrovascular disease.

Abstract: To determine the importance of syphilis testing in cerebrovascular disease, we prospectively assessed 218 consecutive patients with either transient ischemic attack or completed stroke. The results from this study group were compared with those from a control group of 150 neurological patients without cerebrovascular disease. Of 275 patients from both groups specifically tested by the fluorescent treponemal antibody-absorption test, 34% of the study group were seropositive compared with 18% of the controls (^2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Table 2 does not include either syphilis serology or routine chest radiography. Kelley and colleagues reported that even though screening tests for syphilis may be positive the detection of unexpected meningovascular syphilis was very uncommon 30. A similar pattern was found in the Oxfordshire community stroke project.…”
Section: Investigationmentioning
confidence: 69%
“…Table 2 does not include either syphilis serology or routine chest radiography. Kelley and colleagues reported that even though screening tests for syphilis may be positive the detection of unexpected meningovascular syphilis was very uncommon 30. A similar pattern was found in the Oxfordshire community stroke project.…”
Section: Investigationmentioning
confidence: 69%
“…the subtle immunoglobulin abnormalities (OCBs and local IgG synthesis) still detectable in the post-treatment CSF probably do not correlate with the activity of the disease (Fishman, 1992). Although the importance of syphilis testing in cerebrovascular disease has recently been challenged (Kelley et al, 1989). this case emphasizes that the differential diagnosis of stroke in a young man must include syphilis (Johns er al.. 1987).…”
Section: Discussionmentioning
confidence: 93%
“…Syphilis has epidemic proportions in large urban areas on the East Coast of the United States. In Florida, the reported inci dence of syphilis in 1987 was 65.9 per 100,000 persons [8,9], particularly among homosexual men [10], in whom the incidence of primary and secondary syphilis and thus the onset of neurosyphilis has increased since 1985 [8,11], The rise in the incidence of syphilis in the United States is mainly related to an increase in the num ber of cases of cocaine/crack addiction. In 1988, 41% of women with syphilis in Connecticut reported cocaine use [12].…”
Section: Syphilismentioning
confidence: 99%